Makrootoczenie firm z sektora nasiennego roślin rolniczych - Gołębiowski, Bogusław (Macrosurrounding of the Seed Sector Firms of Agricultural Plants, 2005)
The article presents the influence powers of individual factors and processes which reach the surroundings of seed firms of agricultural plants. The problem is presented in the aspect of Poland's accession to the EU as well as new obligatory seed production law.The research was conducted in May 2004. The analysis of conducted research shows off that the economic sphere and the control-legal sphere belong to the stormiest sphere of the seed firms' surroundings. The most propitious sphere for functioning of the company is technological sphere.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 262-266